Assessing the Capability of Sentinel-2A Data for Mapping Seagrass Percent Cover in Jerowaru, East Lombok - Muhammad Afif Fauzan; Ignatius S. W. Kumara; Rifka N. Yogyantoro; Satrio W. Suwardana; Nurul Fadhilah; Intansania Nurmalasari; Santi Apriyani; Pramaditya Wicaksono (Faculty of Geography, Universitas Gadjah Mada, 2017)
Remote sensing technology has been widely used in various applications related to natural resources and environment monitoring. In this paper, we evaluated the capability of new Sentinel-2A image to map the distribution and percent cover of seagrass in optically shallow water of Jerowaru coastal area, East Lombok. Seagrass distribution map was produced from radiometrically and geometrically corrected Sentinel-2A image with overall accuracy of 61.9%. Using empirical model, seagrass percent cover was predicted with maximum coefficient of determination (R2) of 0.51 and standard error of estimate (SE) of 19.4%. The results suggest that Sentinel-2A image can be used to perform seagrass mapping time and cost-effectively and can be further improved by incorporating more robust empirical modeling technique.